Alpha1-antitrypsin protects lung cancer cells from staurosporine-induced apoptosis: the role of bacterial lipopolysaccharide - Natalie Schwarz; Srinu Tumpara; Sabine Wrenger; Evrim Ercetin; Jürg Hamacher; Tobias Welte; Sabina Janciauskiene (Scientific Reports, 2020)
Abstract Elevated levels of plasma alpha1-antitrypsin (AAT) correlate with a poor prognosis of various cancers. Herein, we investigated effects of exogenous AAT on non-small lung cancer cell lines with high (H1975) and very low (H661) baseline expression of SERPINA1 gene encoding AAT protein. Comparison of cells grown for 3 weeks in a regular medium versus medium supplemented with 2 mg/ml of AAT revealed that in the presence of AAT cells acquire better proliferative properties, resistance to staurosporine (STS)-induced apoptosis, and show higher expression of CLU, a pro-tumorigenic gene coding clusterin protein. Similarly, the co-administration of STS with AAT or addition of AAT to the cells pre-treated with STS abrogated effects of STS in both cell lines. Following experiments with H1975 cells have shown that AAT blocks critical steps in STS-induced cell death: inhibition of AKT/MAPK pathways, and activation of caspase 3 and autophagy. AAT does not inhibit apoptosis-triggered by chloroquine (inhibitor of autophagy) or streptonigrin (inducer of p53 pathway). The anti-apoptotic effects of AAT were unaffected by lipopolysaccharide (LPS). However, AAT induced TLR4 levels and enhanced LPS effects on the production of IL-6, a tumor-promoting cytokine. Our data provide further evidence that AAT plays a significant role in the tumorigenesis.